The global challenge : Frameworks for international human resource management - Evans, Paul; Pucik, Vladimir; Barsoux, Jean-Louis. (Boston, Mass McGraw-Hill, 2002)
Through its focus on human resource management and organization, this book provides a guide on how to manage the process of internationalization, with a particular focus on the transnational firm. This book discusses the "people implications" of traditional strategies for internationalization and how such strategies get executed through (HRM)
Keywords: Quản trị kinh doanh